Acute effects of static stretching on characteristics of the isokinetic angle - torque relationship, surface electromyography, and mechanomyography - Cramer, J. T.; Beck, T. W.; Housh, T. J.; Massey, L. L.; Marek, S. M.; Danglemeier, S.; Purkayastha, S.; Culbertson, J. Y.; Fitz, K. A.; Ega, A. D. (Journal of Sports Sciences, 2007)
The aims of this study were to examine the acute effects of static stretching on peak torque, work, the joint angle at peak torque, acceleration time, isokinetic range of motion, mechanomyographic amplitude, and electromyographic amplitude of the rectus femoris during maximal concentric isokinetic leg extensions at 1.04 and 5.23 rad/s in men and women. Ten women (mean ± s: age 23.0 ± 2.9 years, stature 1.61 ± 0.12 m, mass 63.3 ± 9.9 kg) and eight men (age 21.4 ± 3.0 years, stature 1.83 ± 0.11 m, mass 83.1 ± 15.2 kg) performed maximal voluntary concentric isokinetic leg extensions at 1.04 and 5.23 rad/s. Following the initial isokinetic tests, the dominant leg extensors were stretched using four static stretching exercises. After the stretching, the isokinetic tests were repeated. Peak torque, acceleration time, and electromyographic amplitude decreased (P 0.05) from pre- to post-stretching at 1.04 and 5.23 rad/s; there were no changes (P > 0.05) in work, joint angle at peak torque, isokinetic range of motion, or mechanomyographic amplitude. These findings indicate no stretching-related changes in the area under the angle - torque curve (work), but a significant decrease in peak torque, which suggests that static stretching may cause a "flattening" of the angle - torque curve that reduces peak strength but allows for greater force production at other joint angles. These findings, in conjunction with the increased limb acceleration rates (decreased acceleration time) observed in the present study, provide tentative support for the hypothesis that static stretching alters the angle - torque relationship and/or sarcomere shortening velocity.